KONSEP PENYELESAIAN UTANG BERSAMA SUAMI ISTERI DITINJAU MENURUT HUKUM ISLAM DAN HUKUM POSITIF - Furqan Muhammad; Agustin Hanapi (Prodi Magister Hukum Keluarga Pascasarjana UIN Ar-Raniry Banda Aceh, 2023)
When there is a marriage contract, husband and wife are legally bound and bear each other's rights and obligations. Not infrequently in household life, there are often debts carried out by both husband and wife in meeting family needs. In theory, the settlement of joint debt cases seems easy to do. But in fact, there are often protracted and often unresolved problems. The purpose of this study is to find out the concept of joint debt settlement according to Islamic Law and Indonesian Positive Law and to find out how to combine these two concepts in the lives of Indonesian people. This research is library research. The method used in this research is a qualitative method using a juridical-normative approach to understand the laws and regulations; ta'lili reasoning to understand the 'illat of all the provisions of the texts revealed by Allah as well as a comparative approach to compare Islamic Law and Indonesian positive law and find common ground.The results of the study indicate that according to Islamic law, the husband is obliged to pay the debt during the marriage because the husband is the one who is obliged. While according to Positive Indonesian Law, the husband and wife are jointly obliged to pay the family debt based on the union of property during the marriage. These differences can be integrated in the lives of Indonesian people by understanding mutual debt as 'urf which does not conflict with Islamic law and of course to achieve the common good of husband and wife (mashlahah mursalah).